US AGAINST THEM: IDEOLOGICAL AND PSYCHOLOGICAL ASPECTS OF ASHURNASIRPAL II'S CAMPAIGN AGAINST ASSYRIAN REBELS IN ḪALZILUḪA. (December 2020) - Dewar, Ben
Abstract : This paper is a study of the rebellion against the Assyrian king Ashurnasirpal II in the city of Ḫalziluḫa in 882 bc, which is an unusual instance of a rebellion by Assyrians being recorded in the Assyrian royal inscriptions. This paper explores the significance of the rebellion from two angles: the ideological problem of rebellion by Assyrians, and the psychological impact on Assyrian troops of killing their fellow Assyrians. Within the ideology of the royal inscriptions, Assyrians did not normally rebel against the incumbent king, who was in all ways presented as a model ruler. It will be argued that Ashurnasirpal therefore made efforts in his inscriptions to stress that the Assyrian rebels in Ḫalziluḫa inhabited territory that had been lost to Assyria prior to his reign, and had become "de-Assyrianised" and "uncivilised." It will be argued that a similar message was conveyed to the Assyrian soldiers through the ceremonies surrounding the creation of a monument at the source of the River Subnat, and that this message helped the soldiers to "morally disengage" from the act of killing other Assyrians, thus avoiding "moral self-sanctions" for an otherwise morally problematic act.